PROPAGANDA FIREHOSE OF FALSEHOOD PADA PEMILU 2019 DI INDONESIA - Achmad Haqqi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This article discusses the firehose of falsehood propaganda that occurred in Indonesia, in the presidential and vice presidential elections in 2019, was a political campaign strategy that was know effective sufficient to achieve one goal such as what Donald Trump did in elections in the United States of America. The social media burgeoned was so enable for every candidate to use the firehose of falsehood propaganda technique without exception in Indonesia. In the case of the 2019 presidential and vice presidential elections, we can see how campaigns are used on social media such as the spread of hate speech, the emergence of the term kampret, cebong, anti-islam, boyolali,PKI, to hoaxs issues, and so on. What is conveyed contains a minimum of a work program to be achieved, this shows that the two pairs of candidates each use the firehose of falsehood propaganda technique to achieve their goals. The method used in this research is descriptive qualitative which constructivism paradigm  which aims to describe a social phenomenon under study. The date collection method by interviewing, analyzing documentsand using the case study method in the 2019 presidential and vice presidential elections in Indonesia.